10-year stability of clinical-grade serum-free γ-retroviral vector-containing medium - Herbst, Friederike; Ball, Claudia R.; Zavidij, Oksana; Fessler, Sylvia; Schmidt, Manfred; Veelken, Hendrik; Kalle, Christof von; Glimm, Hanno (Gene therapy, 2011)
More than 10 years ago, we developed an efficient protocol for serum-free retroviral transduction of human hematopoietic stem cells derived from mobilized peripheral blood. After upscaling of the methodology, serum-free retroviral gibbon-ape leukemia virus (GALV) pseudotype PG13/LN vector supernatant produced under strict good manufacturing practice (GMP) conditions was used in the first clinical gene-marking trial in Germany. In this study, we analyzed the titer and transduction efficiency of this serum-free clinical-grade retroviral supernatant 10 years after production to evaluate the long-term stability. Long-term storage and transport on dry ice resulted in modestly decreased titers and levels of transduction efficiency in CD34+ cells ranging from 38.4 to 49.1%. We conclude that the stability of retroviral vectors in serum-free medium allows extended storage and distribution of approved clinical-grade retroviral vector stocks to distant sites in multicenter clinical trials.
Published: 11 November 2010
Gesehen am 06.10.2022